2018
DOI: 10.1515/rams-2018-0038
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion and Mechanical Properties of PDMS-Based Materials Probed with AFM: A Review

Abstract: Polydimethylsiloxane (PDMS) is the most widely used silicon-based organic polymer, and is particularly known for its unusual rheological properties. PDMS has found extensive usage in various fields ranging from microfluidics and flexible electronics to cosmetics and food industry. In certain applications, like e.g. dry adhesives or dry transfer of 2D materials, adhesive properties of PDMS play crucial role. In this review we focus on probing the mechanical and adhesive properties of PDMS by means of atomic for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 91 publications
1
30
1
Order By: Relevance
“…The k5 and k10 nanocomposite films’ wettability increased, resulting in more hydrophilic surfaces. Krotil et al and Vlassov et al reported that a silicon tip showed higher adhesive forces with a hydrophilic surface than with a hydrophobic surface, therefore, changes in hydrophilicity resulted in changes in the adhesion values [ 45 , 46 ]. Laitinen et al reported that the interaction forces between the tip and the sample surface depended on surface geometry, and indicated that the value of adhesion increased with increasing surface roughness, which our results confirm [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…The k5 and k10 nanocomposite films’ wettability increased, resulting in more hydrophilic surfaces. Krotil et al and Vlassov et al reported that a silicon tip showed higher adhesive forces with a hydrophilic surface than with a hydrophobic surface, therefore, changes in hydrophilicity resulted in changes in the adhesion values [ 45 , 46 ]. Laitinen et al reported that the interaction forces between the tip and the sample surface depended on surface geometry, and indicated that the value of adhesion increased with increasing surface roughness, which our results confirm [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…PDMS is a synthetic viscoelastic polymer with unusual rheological properties, and converts to a hydrophobic elastomer after curing. [ 158 ] Hydrophilic PDMS can also be fabricated by oxygen plasma treatment and UV radiation of the cured films. [ 159 ] Mechanical properties of the thin film can be tailored by controlling the curing (crosslinking) degree.…”
Section: Substratesmentioning
confidence: 99%
“…In the AFM image, it is possible to capture images from the surface of biodegradable samples with a precision nanometer inline X, Y and an angstrom in Z-direction approving three-dimensional structure and size. The AFM image can provide information on the properties of material surfaces such as hardness and surface adhesion by measuring the forces between the probe and the sample as a function of their mutual separation in AFM analysis that this method is sometimes referred as atomic force spectroscopy (AFS) [51]. As demonstrated in Fig.…”
Section: Characterizationmentioning
confidence: 99%